An Error Analysis In Writing Recount Text Made By Students Of 8th Grade In SMP N 1 Gatak 2015/2016 Academic Year - SARI, Ega Novia; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hidayat, M. Pd (2016)
The aims of this research are: (1) to identify the types of errors in writing recount text made by students of 8th grade in SMP N 1 Gatak 2015/2016 academic year, (2) to identify the types of morphological errors, syntactical errors, and discourse errors, and also count the frequency of each types of errors, (3) to describe the sources of errors. The type of this research is descriptive qualitative research. In collecting data, the researcher uses elicitation technique. In analyzing the data, the researcher uses the theory of James for classifying the errors, and uses Brown‟s theory for sources of the errors. The result of this research shows that in morphological error, there are 67 errors or 33.17% of errors. Then, in syntactical error, the researcher found 132 errors or 65.35% of errors. Lastly, in discourse errors, the researcher found 3 errors or 1.49% of errors. Those errors are divided into two sources, namely interlingual transfer and intralingual transfer.